Challenges and future directions for personal epistemology research in diverse cultures - Wong, B.; Khine, Myint Swe; Sing, C. (Springer Netherlands, 2008)
Beliefs about nature of knowledge and learning, or epistemological beliefs have been an interest of educational researchers and psychologists for the past several years. New perspectives on theoretical, conceptual, and methodological approaches as well as empirical studies on epistemological beliefs are emerging in the literature as a well-defined field of study. Studies show that personal epistemology has influence on comprehension, study strategies, learning process and academic performance. Research in this area has undergone considerable growth in the past decades and has now reached a stage of notable diversity and internationalization. The chapters in this book reported by the educators and researchers from around the world share their experiences in providing theoretical framework and model building and contemporary research on the role of epistemological beliefs in learning. In this concluding chapter the major contributions and salient points by the contributors are summarized and reviewed with a view to clarifying the problems and prospects of further research on epistemological beliefs. © 2008 Springer Science+Business Media B.V.